Photoprotective and anti-inflammatory properties of four Malaysian brown algae in cosmeceuticals - Krishnapriya, Thiyagarasaiyar (2022)
Algae-derived bioactive compounds are receiving global attention as safe and efficient ingredients for development of novel skincare products. This study aimed to evaluate antioxidant, photoprotective, and anti-inflammatory properties of ethanol and water extracts of four Malaysian brown algae, namely, Padina australis, Sargassum polycystum, Sargassum aquifolium, and Dictyota dichotoma, from Port Dickson, Negeri Sembilan. The project was initiated with phytochemical analysis such as total phenolic and flavonoid contents, and antioxidant activities through DPPH radical scavenging and reducing power activities. In addition, the photoprotective and anti-inflammatory properties of algae extracts were evaluated against UVB-induced HaCaT keratinocytes and LPS-induced RAW264.7 macrophage, respectively. The extracts with promising results were further analysed with liquid chromatography-mass spectrometry (LC-MS) to identify the predicted compounds that contributed to cosmeceutical properties. In the present study, all four algae species were reported to have phenolic and flavonoid compounds. The highest phenolic content was found in P. australis ethanol extract (76.04 mg GAE/g), whereas the highest flavonoid content was found in S. polycystum ethanol extract (71.64 mg QE/g). These species reported a significant (p < 0.05) DPPH radical scavenging and reducing power activities, and the highest DPPH radical scavenging and reducing power activities were observed in ethanol extract of S. polycystum (135.96%) and P. australis (162.07%), respectively. Interestingly, a promising photoprotective effect was found in S. aquifolium ethanol extract (400 μg/mL), which exhibited UVB protective effect through downregulation of COX-2 (1.2-fold) and MMP-1 (3.1-fold) expression in UVB-induced HaCaT keratinocytes. Furthermore, S. aquifolium ethanol extract (625 μg/mL) showed a promising anti-inflammatory effect through downregulation of iNOS via NO suppressions and inhibited inflammatory cytokines such as TNF-α (45%) and IL-6 (98%). In addition, LC-MS analysis detected that S. aquifolium ethanol extract consists of carbohydrates, fats, carotenoids, terpene, pigments, benzofuran, and phloroglucinol. In summary, bioactive metabolites derived from S. aquifolium have been shown to exhibit better antioxidant, antiphotoaging, and anti-inflammatory effects. Therefore, S. aquifolium could be considered as a promising source and can play significant role in cosmeceuticals development.